Do Students’ Self -Confidence affect to Their Speaking Performance? : The Correlation Study - nasruddin roziq ali (Language-Edu, 2020)
This study was conducted to see the correlation between students’ self-confidence and their speaking performance in speaking class of fourth-semester students.   It is intended to get the data about whether a statistically significant correlation between self-confidence and speaking performance. This research design was the correlation method. Toward data collection technique in this research was questionnaire and document study. The questionnaire was to measure students’ self-confidence and documents study to observe about their speaking performance.  Furthermore, the data were analyzed by applying analysis factor to classify the factor which conducted from self-confidence (Awareness, Capability, and Belief) and regression analysis which aimed to see the regression between three factors as the independent variable and students’ speaking performance as the dependent variable.  From regression calculation result showed that the F value 1.760 < 3.91, Sig score .157b > 0.05 and T scores (awareness 0.008, capability 0.533, believe 1.845) < 1.976. Thus, it can be concluded that self-confidence has low significant correlate with speaking performance. Then, based on the result, it is suggested that lecturers need the lecturers are suggested to facilitate and activate students' linguistic intelligence by fortifying their grammatical and vocabulary in the learning process. For the future researcher, this topic is quite general the researcher suggests doing deep investigations about the relationship between self-confidence and speaking performance aims to get details by using different statistical that such as factor analysis and multiple regressions to obtain the information more detailed about these relationships with more specific instruments. Therefore, the researcher also suggests applying add spoken test as the kind of better research instrument accompanies with make students classification belongs to the level of students’ confidence and speaking performance.Keywords: Self -Confidence, Speaking Performance